1971
DOI: 10.1021/ac60307a042
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ionization mass spectrometry

Abstract: Del. 19711 /'"'hemical ionization (Cl) mass ^spectrometry is a relatively new technique for the production of mass spectra of compounds in which the ions from the molecules of interest are formed by ion-molecule reactions. The method of ion pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…That is, the resulting CI mass spectra produce ions characteristic of the EI mass spectra with decreasing proton affinity of the reagent gas. 12 A similar pattern was exhibited by CI mass spectra of M-4365 A2 (2) as indicated in Table 1, except for the de-epoxidation process ( m / z 582+ m / z 566).…”
Section: Chemical Ionization Mass Spectra Of M-4365 Gz and A2supporting
confidence: 74%
“…That is, the resulting CI mass spectra produce ions characteristic of the EI mass spectra with decreasing proton affinity of the reagent gas. 12 A similar pattern was exhibited by CI mass spectra of M-4365 A2 (2) as indicated in Table 1, except for the de-epoxidation process ( m / z 582+ m / z 566).…”
Section: Chemical Ionization Mass Spectra Of M-4365 Gz and A2supporting
confidence: 74%
“…The use of ionization techniques causing negligible fragmentation such as field ionization (19), chemical ionization . (20), or low-voltage electron-impact ionization (21) seems to be the obvious experimental approach to this problem. Apart from the earlier mentioned experiments with high resolution field ionization mass spectrometry ( I @ , we are at present engaged in low-voltage electron-impact ionization studies, which also encompass higher mass ranges than the study reported here (22).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical ionization mass spectra of sample molecules are typically simple and they often consist of the molecular ion (M+ or MH2+ with little concomitant fragmentation. Therefore, chemical ionization mass spectrometry has enjoyed considerable application in the areas of quantitative and qualitative analysis (51)(52)(53).…”
Section: Gas Chromatography Of Metal Complexesmentioning
confidence: 99%